Harmonization of Interfaith Marriage Law in Indonesian Legal System : Between Social Reality and Legal Certainty - Fitri Yanti Katili; Qisthy Leonarza; Fadlan Fadlan (International Journal of Social Welfare and Family Law, 2025)
The legal landscape of interfaith marriage in Indonesia presents a complex challenge that intersects social dynamics, legal frameworks, and cultural diversity. This research aims to critically analyze the existing legal system governing interfaith marriages, exploring the fundamental tensions between legal norms and social realities. Through a comprehensive socio-legal methodology, the study investigates the intricate challenges of harmonizing marriage laws in a pluralistic society.The research employs a mixed-method approach, combining normative juridical analysis with empirical social research. Extensive document analysis, comparative legal studies, and expert interviews provide a nuanced understanding of the current legal and social complexities surrounding interfaith marriages. The study examines the interactions between state law, religious norms, and customary traditions that shape marriage regulations in Indonesia.Key findings reveal significant gaps between legislative provisions and social practices, highlighting the urgent need for a more adaptive and inclusive legal framework. The research identifies multiple challenges, including jurisdictional conflicts, individual rights protection, and the complex interplay of different normative systems. Theoretical foundations draw from legal certainty theory, legal pluralism, and social justice theory to construct a comprehensive analytical framework.The study proposes innovative approaches to legal harmonization, emphasizing the delicate balance between maintaining legal certainty and accommodating social realities. Recommendations include developing more flexible legal mechanisms, enhancing inter-institutional dialogue, and creating regulatory frameworks that recognize the dynamic nature of social relationships and individual rights in contemporary Indonesian society.Ultimately, the research demonstrates that effective legal harmonization requires a holistic approach that bridges the gap between formal legal structures and the lived experiences of individuals navigating interfaith marriages. By providing a critical analysis of the current legal landscape, the study contributes to broader discussions on legal pluralism, social justice, and individual rights in Indonesia.